2018
DOI: 10.1097/tp.0000000000002270
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Initiated Everolimus on the Recurrence of Hepatocellular Carcinoma After Liver Transplantation

Abstract: Everolimus may not be universally prescribed to prevent tumor recurrence in liver transplant patients with hepatocellular carcinoma. Future randomized trials should be focused on patients with histological features of increased tumor aggressiveness, in whom the potential benefit would be higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 27 publications
0
60
0
Order By: Relevance
“…A longer follow-up is required to better determine renal function improvement and may permit an assessment of other potential advantages of an mTOR inhibitor-based regimen, such as a decreased recurrence of HCC, although a recent finding did not support the prescription of EVR in HCC LT recipients due to no significant benefit in terms of tumor recurrence. (36) In conclusion, an immunosuppressive schedule with very early (7 days) introduction of EVR in association with TAC reduction and/or withdrawal was associated with a significant improvement of renal function as early as 3 weeks after transplantation and persisting up to 24 months. However, this regimen was associated with higher incidence of wound complications, lipid profile modifications, and proteinuria.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A longer follow-up is required to better determine renal function improvement and may permit an assessment of other potential advantages of an mTOR inhibitor-based regimen, such as a decreased recurrence of HCC, although a recent finding did not support the prescription of EVR in HCC LT recipients due to no significant benefit in terms of tumor recurrence. (36) In conclusion, an immunosuppressive schedule with very early (7 days) introduction of EVR in association with TAC reduction and/or withdrawal was associated with a significant improvement of renal function as early as 3 weeks after transplantation and persisting up to 24 months. However, this regimen was associated with higher incidence of wound complications, lipid profile modifications, and proteinuria.…”
Section: Discussionmentioning
confidence: 72%
“…It may be useful to analyze a subpopulation with poor renal function to verify the opportunity to anticipate EVR conversion also in this setting. A longer follow‐up is required to better determine renal function improvement and may permit an assessment of other potential advantages of an mTOR inhibitor–based regimen, such as a decreased recurrence of HCC, although a recent finding did not support the prescription of EVR in HCC LT recipients due to no significant benefit in terms of tumor recurrence …”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge the two open-label studies highlighted by Rodríguez-Perálvarez et al, which displayed drug withdrawal rates of 23%-26%. 7,8 Conversely the SILVER trial showed similar rates of all and serious adverse events between mTOR-and calcineurin-inhibitors. 6 Notably, the reported side effects of mTOR-inhibitors in liver transplant patients are likely independent of the indication for use (eg renal protection vs recurrence prevention).…”
Section: R E Fe R E N C E Smentioning
confidence: 95%
“…Furthermore, EVR had been shown to exert antiproliferative effects and antitumor activity on hepatoma cells in vitro . However, in either clinical or in vivo trials, clear evidence is still missing confirming that the application of EVR could reduce recurrence rates of hepatocellular carcinoma (HCC) after LT . New evidence suggests that EVR protects LT patients from the development of donor‐specific antibodies, which may complicate longterm graft viability .…”
mentioning
confidence: 99%
“…(1)(2)(3) Furthermore, EVR had been shown to exert antiproliferative effects and antitumor activity on hepatoma cells in vitro. (4,5) However, in either clinical or in vivo trials, clear evidence is still missing confirming that the application of EVR could reduce recurrence rates of hepatocellular carcinoma (HCC) after LT. (6)(7)(8) New evidence suggests that EVR protects LT patients from the development of donor-specific antibodies, which may complicate longterm graft viability. (9,10) Moreover, the administration of EVR is related to a reduction in the risk of cytomegalovirus infections among immunosuppressed patients (11)(12)(13) and has been shown to reduce the viral load of LT patients infected with hepatitis C virus genotypes 2a and 3.…”
mentioning
confidence: 99%